2011
DOI: 10.1007/s00784-011-0545-8
|View full text |Cite
|
Sign up to set email alerts
|

Transmigration of impacted canines: prevalence, management and implications on tooth structure and pulp vitality of adjacent teeth

Abstract: The aim of this study was to estimate the prevalence of transmigrant canines in a sample of panoramic radiographs of a random Greek population, to classify them and evaluate clinically and radiographically all the implications for adjacent teeth. Panoramic radiographs of 3,586 patients retrieved from eight private practices between 1998 and 2009, were examined. Panoramic radiographs with extracted canines were not included in this study. An impacted canine was considered to be transmigrant when at least part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 28 publications
(59 reference statements)
3
32
0
6
Order By: Relevance
“…In the present article, transmigration was diagnosed in adolescent girls. Other authors have also noted that the complication occurs more frequently in female patients and usually develops during puberty [4,7,19,20]. One of the cases described above involved a very rare bilateral displacement of canines in the mandible - three of the four transmigrating canines had been displaced from the left to the right side.…”
Section: Discussionmentioning
confidence: 94%
“…In the present article, transmigration was diagnosed in adolescent girls. Other authors have also noted that the complication occurs more frequently in female patients and usually develops during puberty [4,7,19,20]. One of the cases described above involved a very rare bilateral displacement of canines in the mandible - three of the four transmigrating canines had been displaced from the left to the right side.…”
Section: Discussionmentioning
confidence: 94%
“…There are various studies in the literature related to impacted and transmigrated teeth [17,18,20,29-37], but only a few comprehensive studies are available. As found in previous reports, canine impaction is more prevalent in the maxilla than the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Mazinis et al 27 reported six mandibular TCs, which all of them were fully impacted, and no maxillary TCs in 3586 patients. Aydın et al 21 reported 8 mandibular and 6 maxillary TCs in 4500 patients and except for maxillary one, the rest of the TCs were fully impacted.…”
Section: Discussionmentioning
confidence: 99%
“…These are observation, surgical extraction, transplantation, bringing to the original position of the unerupted canine by surgical and orthodontic treatment 18,27,28,30 .…”
Section: Discussionmentioning
confidence: 99%